The Effect of Hypnobirthing Techniques on The Delivery of Labor Process and The Level of Pain in Mother - Sumita Ambarita; Merice Simarmata (JURNAL KEBIDANAN KESTRA (JKK), 2023)
The intensity of labor pain as much as 91.9% of women experience pain during labor. The method used to reduce pain is hypnobirthing. Hypnobirthing is a method of self-hypnosis and relaxation techniques to make it easier for expectant mothers to give birth. A cross sectional study approach was used in this research. The results stated that there was an effect of hypnobirthing on the length of labor with p<0.002. The results of the test on pain showed that there was a significant effect between hypnobirthing techniques on the level of labor pain with p value (0.002) < (0.05), the frequency of pain intensity indicated that many mothers in labor did not experience pain. The hypnobirthing technique has an alternative as a solution to public health problems in systems thinking, especially in the field of midwifery health policy where community empowerment and midwives to improve public health degrees provide knowledge for the general public in the field of hypnobirthing techniques, in labor and delivery processes. the level of pain in mothers who want to give birth, and reduce the number of cesarean sections.